Lessons we should have learned from the global financial crisis but didn't - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
In this paper, I first quickly recount the causes and consequences of the global financial crisis (GFC). Of course, the triggering event was the unfolding of the subprime crisis; however, I argue that the financial system was already so fragile that just about anything could have caused the collapse. I then move on to an assessment of the lessons we should have learned. Briefly, these include: (a) the GFC was not a liquidity crisis, (b) underwriting matters, (c) unregulated and unsupervised financial institutions naturally evolve into control frauds, and (d) the worst part is the cover-up of the crimes. I argue that we cannot resolve the crisis until we begin going after the fraud. Finally, I outline an agenda for reform, along the lines suggested by the work of Hyman P. Minsky.
Keywords: E3; E11; E12; E32; E44; G01; G21; G38; 330; global financial crisis; subprime crisis; Hyman P. Minsky; Galbraith and the Great Crash; control fraud; underwriting; deregulation; financial reform